The Prevalence of Dairy Goat’s Subclinical Mastitis Related to Udder Morphology and Farming Management Practices - Khasanah, Himmatul; Yulianto, Roni; Widodo, Nur; Widianingrum, Desy Cahya; Rusdiana, Riza Yuli (Jurnal Sain Veteriner, 2024)
This study aimed to analyze the prevalence of subclinical mastitis (SCM) and the correlation between CMT positive score, udder morphology and management practice in dairy goats in several regencies in East Java. The SCM identification was tested using the California Mastitis Test (CMT) method. The obtained data were analyzed qualitatively and quantitatively, and the correlation was determined using Kendall’s tau_b coefficient correlation method. The results showed the prevalence of SCM in Blitar, Lumajang, and Jember amounted to 19,35%, 0,86%, and 25%, respectively. The control management of observed dairy farms was relatively similar such as the milking frequency, feeding management, health control, and cage type. Milk production was moderately correlated with CMT (tb =-0.417) and low correlation with the udder shape (tb =1.51), side udder cross-section (tb =-0,293), teat angle of separation between teat (tb =0,204), and degree of udder separation (tb =0,128). The CMT also has low correlation with the BCS (tb =0,146), udder symmetry (tb =0,126), sided udder cross-section (tb =0,153). Then CMT also has a moderate correlation with housing type (tb =-0,380) and milking frequency (tb =0.365). In conclusion, the prevalence of SCM was relatively low to moderate and its correlation with udder morphology were low to moderate.